Study of gene flow from gm cotton (gossypium hirsutum) varieties in “el espinal” (tolima, colombia). (2013)
In 2009, 4088 hectares of genetically modified (GM) cotton were planted in Tolima (Colombia), however there is some uncertainty about containment measures needed to prevent the flow of pollen and seed from regulated GM fields into adjacent fields. In this study, the gene flow from GM cotton varieties to conventional or feral cotton plants via seed and pollen was evaluated. ImmunostripTM, PCR and ELISA assays were used to detect gene flow. Fifty six refuges, 27 fields with conventional cotton and four feral individuals of the enterprise “Remolinos Inc.” located in El Espinal (Tolima) were analyzed in the first half of 2010. The results indicated seeds mediated gene flow in 45 refuges (80,4 %) and 26 fields with conventional cotton (96 %), besides a pollen mediated gene flow in one field with conventional cotton and nine refuges. All fields cultivated with conventional cotton showed gene flow from GM cotton. Two refuges and two feral individuals did not reveal gene flow from GM cotton.